Compulsory Medical Measures in the Criminal Code of the Russian Federation (Ius Novum, 2026)
This paper presents an overview of the subject matter. Its purpose is to discuss the scope of the provisions on compulsory medical measures contained in the 1996 Criminal Code of the Russian Federation (referred to in Polish law as ‘preventive therapeutic measures’). The following methods were used in drafting this study: an analysis of legal sources, i.e. the 1996 Criminal Code of the Russian Federation, and an analysis of (legal) literature. The paper outlines the rationale for the use of compulsory medical measures, as well as their purposes and types. Particular attention is paid to the analysis of solutions associated with forced outpatient observation and psychiatric treatment, as well as forced treatment in a psychiatric hospital (which has a problematic history in Russia). The issues related to the modification of the use of these measures are also addressed. For the purposes of this article, the following hypothesis was adopted: ‘The scope of the provisions on compulsory medical measures contained in the 1996 Criminal Code of the Russian Federation is broad and includes numerous measures that are regulated in detail.’ The research, which partially confirmed this article hypothesis, shows that the scope of the analysed provisions on compulsory medical measures contained in the 1996 Criminal Code of the Russian Federation is not broad and has some shortcomings.